2007
DOI: 10.1177/0048393107299684
|View full text |Cite
|
Sign up to set email alerts
|

Unrealistic Assumptions in Rational Choice Theory

Abstract: The most common argument against the use of rational choice models outside economics is that they make unrealistic assumptions about individual behavior. We argue that whether the falsity of assumptions matters in a given model depends on which factors are explanatorily relevant. Since the explanatory factors may vary from application to application, effective criticism of economic model building should be based on model-specific arguments showing how the result really depends on the false assumptions. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 49 publications
0
40
0
Order By: Relevance
“…When this occurs, it is of course necessary to say something in defense of any false assumptions incorporated via the analogy. An example of attempting to defend false assumptions within analogical models comes from Aki Lehtinen and Jaakko Kuorikoski's discussion of the unrealistic assumptions carried over in the application of rational choice theory outside of economics (Lehtinen and Kuorikoski 2007). The authors contend that, ''the assumption of self-interest is not explanatorily important in a model if it can be replaced with another behavioral assumption without changing the analytical results.…”
Section: Analogical Modelingmentioning
confidence: 99%
“…When this occurs, it is of course necessary to say something in defense of any false assumptions incorporated via the analogy. An example of attempting to defend false assumptions within analogical models comes from Aki Lehtinen and Jaakko Kuorikoski's discussion of the unrealistic assumptions carried over in the application of rational choice theory outside of economics (Lehtinen and Kuorikoski 2007). The authors contend that, ''the assumption of self-interest is not explanatorily important in a model if it can be replaced with another behavioral assumption without changing the analytical results.…”
Section: Analogical Modelingmentioning
confidence: 99%
“…In this, it presents an interesting challenge to philosophers of economics to develop more sophisticated views of qualified realisticness which admit partiality, provisionality, and progressiveness. This project will undoubtedly need to address prominent views on realisticness in economic models, such as Lehtinen and Kuorikoski's (2007), and Mäki's (2009). Refocusing modelling from equilibrium to organization seems to be fertile ground for this discussion for those who find the claims of greater realisticness intuitively appealing but in need of much work.…”
Section: Eindhoven University Of Technologymentioning
confidence: 99%
“…It will be demonstrated that derivational robustness was a main reason why economists initially thought the stability literature was positive-why it increased confidence in the Walrasian general equilibrium model-but 7 This is a modified version of the characterization of robustness in Odenbaugh and Alexandrova, (2011, p. 764). 8 The recent literature supporting various types of robustness analysis in economics includes: Guala and Salanti 2003;Kuorikoski and Lehtinen 2009;Kuorikoski et al 2010Kuorikoski et al , 2012Lehtinen and Kuorikoski 2007;Lehtinen and Marchionni 2011;Weisberg 2013;and Woodward 2006. For critical remarks on robustness analysis see Cartwright (1991Cartwright ( , 2007Cartwright ( , 2009), Odenbaugh andAlexandrova (2011), andReiss (2012).…”
Section: Introductionmentioning
confidence: 99%